2021
DOI: 10.1016/j.psj.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental conditions during transport on chick weight loss and mortality

Abstract: The present study had 2 objectives: the first was to analyze the possible impact of transport on weight loss and mortality during transport, and first-week mortality. The second was to monitor the environmental condition (i.e., temperature, humidity, and so on) variability during transport with an effect on day-old chicks. Probe equipment was installed in a truck of a poultry company from Spain, including a total of 66 journeys made in commercial conditions between May and November 2017. Animal-based measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…In a study from Yerpes et al. (2021) in Spain, including a total of 66 journeys made in commercial conditions between May and November 2017, the mean chick mortality during transport was 0.055% (SD = 0.043). The literature about specific DOA of day‐old chicks is very scarce, so from this recent paper, it can be assumed that DOA is not exceeding 0.1%.…”
Section: Assessment Of Scenario 2: Road and Air Transport Of Day‐old ...mentioning
confidence: 98%
See 1 more Smart Citation
“…In a study from Yerpes et al. (2021) in Spain, including a total of 66 journeys made in commercial conditions between May and November 2017, the mean chick mortality during transport was 0.055% (SD = 0.043). The literature about specific DOA of day‐old chicks is very scarce, so from this recent paper, it can be assumed that DOA is not exceeding 0.1%.…”
Section: Assessment Of Scenario 2: Road and Air Transport Of Day‐old ...mentioning
confidence: 98%
“…Therefore, the cause of DOA might not need to be investigated for each individual transport, but if it exceeds a certain level, that might be attributed to the transport conditions. In a study from Yerpes et al (2021) in Spain, including a total of 66 journeys made in commercial conditions between May and November 2017, the mean chick mortality during transport was 0.055% (SD = 0.043). The literature about specific DOA of day-old chicks is very scarce, so from this recent paper, it can be assumed that DOA is not exceeding 0.1%.…”
Section: Iceberg Indicatorsmentioning
confidence: 99%
“…Drying of chicks after hatching or spray vaccination is also a prerequisite for avoiding chicks staying wet and being exposed to too low effective temperature. Upon arrival on the broiler farm, pre-heating of the barn and controlling ventilation to get the appropriate environmental temperature (30-35°C) upon placement and during the first days of life is essential to prevent cold stress (Karcher, 2021;Yerpes et al, 2020Yerpes et al, , 2021. Alternatively, dark brooders or brooding rings can be used with a temperature of 32-35°C at the edge of the dark brooder as heating source (Aviagen, 2018a).…”
Section: Day-old Chicks Hatched In Hatcherymentioning
confidence: 99%
“…This study agrees with what [15], indicated that stressed birds As a result of the transportation process and the temperature rising above the natural limits, they resort to cooling their bodies by evaporating water through the respiratory system and thus increasing the breathing rate, and this in turn leads to dehydration and thus a decrease in weight. It is worth noting that broilers do not contain sweat glands, so thermoregulation may fail during stress Convection, thus accumulating heat and increasing the temperature it is forced to increase the respiration rate to lower the body temperature and dehydration occurs leading to weight loss [16], [17], [18]. To mitigate the harmful effect of transport stress and heat stress, several attempts were implemented using medicinal plants, through dietary intervention through feed and drinking water.…”
Section: Discussionmentioning
confidence: 99%